Causal association of immune cells and endometritis: a Mendelian randomization study - Li, Jing-wei; Wan, Ren-tao; Liu, Qing-dong; Xu, Hong-lin; Chen, Qi (Scientific reports, 2024)
Research exploring the link between immune cell profiles and the development of endometritis remains scant. This gap necessitates further study to decode the complex interrelations influencing this condition. In this analysis, we leveraged two-sample Mendelian randomization to examine the causal ties between the phenotypes of immune cells and the incidence of endometritis. Our evaluation hinged on data from 3757 participants hailing from Sardinia, focusing on a diverse array of 731 immune phenotypes, and cross-referenced with endometritis data sourced from the UK Biobank. To ensure rigor, we performed sensitivity analyses, utilized MR-Egger and MR-Presso to check for pleiotropy, and applied Cochran’s Q test for assessing the heterogeneity of our findings. Our investigation identified numerous immune characteristics associated with endometritis. For certain immune traits, a lower risk of endometritis was observed, including: Absolute Counts of CD39 + CD4 + T cells, CD25 + CD39 + CD4 regulatory T cells, and CD25 + + CD8 + T cells; Absolute Counts of Switched Memory B cells; CD19 expression on IgD + CD38dim and Switched Memory B cells; CD20 expression on IgD + CD38− Unswitched Memory B cells; percentage of Switched Memory B cells among lymphocytes; CD16-CD56 expression on HLA DR + Natural Killer cells; percentage of CD11c + CD62L− monocytes; CD86 expression on monocytes; CCR2 expression on CD14 + CD16 + monocytes; and CD14 expression on Monocytic Myeloid-Derived Suppressor Cells, with Odds Ratios (ORs) between 0.413 and 0.703. On the contrary, increased risks of endometritis were linked with: the percentage of Effector Memory CD4 + T cells within the CD4 + T cell population; percentages of HLA DR + T cells and HLA DR + CD8 + T cells among T cells; CD4 expression on CD28 + CD4 + T cells; CD20 expression on CD20- CD38- B cells; percentage of IgD + CD24 + B cells within the B cell population; CD62L expression on CD62L + myeloid Dendritic Cells; and Absolute Counts of Plasmacytoid Dendritic Cells, with ORs from 1.473 to 2.677, indicating these traits potentially elevate the risk of developing endometritis. Our research delineates distinct causal links between specific immune cell phenotypes and endometritis, offering new perspectives that could contribute to the pinpointing of new therapeutic avenues for this condition.